The Clinical Significance of FilmArray Respiratory Panel in Diagnosing Community-Acquired Pneumonia. (6th September 2017) - Chen, Huanzhu; Weng, Huilan; Lin, Meirui; He, Ping; Li, Yazhen; Xie, Qingdong; Ke, Changwen; Jiao, Xiaoyang
Abstract : Aim . FilmArray Respiratory Panel (FilmArray RP) test is an emerging diagnostic method in fast detecting multiple respiratory pathogens; the methodology and clinical significance of FilmArray RP in community-acquired pneumonia (CAP) diagnosis were evaluated in this study. Methods . Specimens from 74 patients with CAP were analyzed and compared using FilmArray RP, traditional multiple PCR assay, bacterial (or fungal) culture, and serological detection. Results . FilmArray RP and multiplex PCR showed 100% coincidence rate in detecting coronaviruses 229E, OC43, HKU1, and NL63, human metapneumovirus, influenza A and B, and parainfluenza viruses (PIV1, PIV2, and PIV4). There were 15 viral specimens tested as disagreement positive results. FilmArray RP had higher detection rate in detecting dual viral and Mycoplasma pneumoniae infection. The positive bacteria (or fungi) were found in 25 specimens. Conclusions . This study demonstrated the capability of FilmArray RP for simultaneous detection of broad-spectrum respiratory pathogens and potential use in facilitating better patient care.